Nesting Substrate Characteristics of Partamona seridoensis Pedro & Camargo (Hymenoptera: Apidae) in Areas of Dry Forest in Brazil - Fernandes, Carlo Rivero Moura; Almeida, Alerson Brito; Del Lama, Marco Antonio; Martins, Celso F (Sociobiology, 2017)
For the first time the association between Partamona seridoensis and Constrictotermes cyphergaster is described. Partamona seridoensis occurs in xeric areas of Northeastern Brazil, and it is a termitophile species as its nests are built in active and inactive arboreal termite nests of the species C. cyphergaster. This study aimed to verify the characteristics of the nesting substrate used by P. seridoensis in two areas of dry forest (caatinga) in Cariri region, Paraíba state. It has been found that the vertical distribution of termites that contained colonies of P. seridoensis varied from 10 cm to 3.60 m, while the height of the nest entrance varied from 20 cm to 3.70 m. Commiphora leptophloeos, popularly known as imburana, was the support tree of 22 (43.1%) from 51 observed termite nests that harbored bee colonies. Most (44; 86.2%) of the host termites colonies were active. Most of the colonies showed the nest entrances not directed to the east/southeast. All colonies located were housed in large termite nests, whose volumes exceed 30 liters. In the two areas surveyed, frequently the entrances of the nests were directed to other nearby colonies, suggesting a parental relationship that should be further investigated.